Short-term inhibitory effects of TiO2 NPs on Anammox process - (:unkn) unknown (My University, 2020)
Anammox process has brought about cost-effective, eco-friendly, and innovativetechnologies to wastewater treatment by reducing the operational cost of treatmentplants and decreasing greenhouse gas emissions. Titanium dioxide (TiO2), as one of themost prevalent nanoparticles (NPs) in the world, is being used in various consumerproducts and applications. In recent years, studies have focused on potentialtoxicological impacts of NPs on biological processes due to their endless productionand consumption. In this context, the first time in the literature, 24 h acute TiO2 NPsexposure on Anammox process was investigated. Deterioration on anammox activitygradually increased with increasing applied TiO2 NPs concentration. At 300 mg/Lexposure dose, nitrogen removal rate dramatically decreased to 37.09 ± 0.24 mgN/gVSS.d and a severe inhibition (80.57% ± 1.17%) was observed. Among the severalcurve fit models, non-linear second order polynomial (quadratic) model was the bestfit one with IC50 of 154 mg/L. Scanning electron microscope (SEM) imagesdemonstrated the tendency of TiO2 NPs to aggregate and attach to the surface of thebacteria. Extracellular polymeric substance (EPS) response of anammox bacteria wasalso investigated and it was found that, the total EPS content gradually decreased byincreasing TiO2 NPs concentration.